Higher Education for Good: Teaching and Learning Futures. - Agherdien, Najma; Rahiman, Fatima (Critical Studies in Teaching and Learning, 2024)
Cronin, C. and Czerniewicz, L. (eds.). 2023. Higher Education for Good: Teaching and Learning Futures. Cambridge: Open Book Publishers.